Caribbean Crazy Ant (proposed common name), Paratrechina pubens Forel (Insecta: Hymenoptera: Formicidae: Formicinae) - John Warner; Rudolf H. Scheffrahn (EDIS)
Over the last few years reports have escalated of a golden-brown to reddish-brown "crazy ant" infesting properties in and around West Palm Beach, Florida. Thick foraging trails with thousands of ants occur along sidewalks, around buildings, and on trees and shrubs. Pest control operators using liquid and/or granular broad-range insecticides appear unable to control this nuisance ant. This document is EENY-284 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2003. Revised: February 2004.